The Once and Future Library - Gerry McKiernan (Issues in Science and Technology Librarianship)
In Fall 1995, a World Wide Web (WWW) virtual library was established to investigate the applicability of using a conventional library classification scheme as an organizational framework for enhancing identification, access and use of Internet resources (McKiernan 1995). Named CyberStacks(sm), this service has adopted an outline of the Library of Congress classification schedules as a system for indicating broad and specific relationships among selected Net resources. This article describes CyberStacks(sm) and highlights advantages and limitations of this resource.